Patient confidentiality within the context of group medical visits: is there cause for concern?. (9th December 2013) - Wong, Sabrina T.; Lavoie, Josee G.; Browne, Annette J.; MacLeod, Martha L. P.; Chongo, Meck
Abstract: Background: Group medical visits (GMVs), clinical encounters with a medical component delivered to groups of patients, have emerged as an innovative approach to potentially increasing efficiency while enhancing the quality of primary health care (PHC). GMVs have created the need to pay explicit attention to patient confidentiality. Objective: What strategies are used by providers and patients to address issues of confidentiality within GMVs? Design: In‐depth interviews were conducted with 34 PHC providers and 29 patients living in nine rural communities in British Columbia, Canada. Data were analysed using interpretive thematic analysis and a relational autonomy approach. Results: We found three main themes: (i) choosing to disclose: balancing benefits and drawbacks of GMVs, (ii) maintaining confidentiality in GMVs and (iii) gaining strength from interdependent relationships: patients learning from each other. Confidentiality can be addressed and was not a major concern for patients attending or providers facilitating GMVs in these rural communities. Discussion: Patients adopted strategies to address their own and others' concerns related to confidential health information. Providers used multiple strategies to maintain confidentiality within the group, including renegotiating what information is shared and providing examples of what information ought to be kept confidential. Conclusions: Although GMVs are not for all patients, a relational autonomy approach is useful in drawing attention to the context and structures which may influence their patients' ability to act autonomously. Successful delivery of GMVs requires both patients and providers to negotiate between maintaining confidentiality and an appropriate level of disclosure.